Innovative stainless-steel connector for double-tee girders under various loading conditions - Young, Trevor (Kansas State University, 2021)
Steel connections embedded in the flanges of precast double-tee concrete girders are a common type of connection to join precast elements together to create floor diaphragm systems in structures such as parking garages. These steel connections are the main load transferring elements in precast structures and have been observed to be inadequate needing repairs after being in service due to high load demands. The main objective of this research was to evaluate the strength of a newly designed stainless-steel connector as a repair solution for failing embedded connections in preexisting precast structures. The connectors were embedded into the edges of concrete prototype slabs to simulate the behavior of the connector when it was embedded into the sides of the flanges of precast double-tee concrete girders. An experimental program was developed to determine the load capacity of the connector and its embedment as deformation occurred. The procedure involved monotonic tests for axial tension, horizontal shear, and vertical shear followed by cyclic tests for horizontal shear and vertical shear. In addition, a flexural capacity test was performed on two slabs adjoined by the proposed connector. Very promising results are generated indicating a superior behavior for this connector compared to the state-of-the-art detail. The observed experimental capacities of the connectors are paired with some analytical models to support the overall strength development determined for the connectors.
Keywords: Shear connectors; Double-tee concrete girders; Precast concrete; Various load conditions